An experimental study of a novel liquid carbon dioxide rock-breaking technology. (April 2020) - Li, Qi-Yue; Chen, Guan; Luo, Da-You; Ma, Hai-Peng; Liu, Yong
Abstract: Safely and high-efficiently breaking rock is of practical significance. In some engineering, explosive blasting may be restricted for its side effects. Traditional non-explosive methods like demolition agent and rock breaking machine are generally time-consuming. Therefore, this study proposes a novel liquid carbon dioxide rock-breaking technology and designs the relative device. The effectiveness, safety and high-efficiency of the proposed technology are investigated by shock pressure test, vibration site test and field rock breaking experiment. The experimental results show that the duration of the monitoring shock pressure is around 1500 μs. The shock pressure signal of liquid carbon dioxide tube breaking in free condition contains four stages, namely, increasing exponentially, decreasing oscillatory, stabilization, and negative pressure stage. As pressure sensor is set at 850 mm from the test tube radially, the shock pressure monitored increases to the maximum value of 115.7 kPa within 6 μs. During the liquid carbon dioxide rock breaking, the vertical component of the peak particle velocity of vibration is 173 mm/s, 85 mm/s and 35 mm/s along distance at 1.5 m, 2.5 m and 3.5 m from the tube, respectively. The Fourier power spectra results show that about 85% energy distributes at 6–60 Hz. The vibration caused by the novel technology can meet the requirement of mainstream blasting safety criteria better than that of explosive blasting. Finally, the technology is successfully applied in rock excavation at a metro station construction site. The proposed liquid carbon dioxide rock-breaking technology is preliminarily demonstrated to be safer than explosive blasting and more efficient than traditional non-explosive techniques.